Древности салтовского круга в смоленских длинных курганах - Нефёдов, В.С. (Хазарский альманах, 2020)
The author studies the metalic artefacts of Saltovo origin and their imitations found in the graves of Long barrows culture from the 8th–10th cent. in Smolensk region – details of belts, ornaments and household objects – totally ca. 50 fi nds from 13 cemeteries. The chronological analysis demonstrate that Saltovo artefacts were widespread in the Eastern part of Smolensk Long barrows culture almost during the whole period of its existence, from early to late graves. Maximum of the penetration of these objects in Smolensk part of Dniepr basin falls to the 2nd half of the 8th – the 1st half of the 9th cent. The author supposes that Saltovo artefacts were imported to the studying region generally through the Upper Seim and the Upper Oka basins, which was inhabited by Slavonic population of Romny culture. However there were also direct connections between inhabitants of the south-west regions of the Khazar Khaganate and the Slavonic population built Smolensk long barrows.